2016
DOI: 10.1016/j.cels.2016.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Network Architecture Predisposes an Enzyme to Either Pharmacologic or Genetic Targeting

Abstract: SUMMARY Chemical inhibition and genetic knockdown of enzymes are not equivalent in cells, but network-level mechanisms that cause discrepancies between knockdown and inhibitor perturbations are not understood. Here we report that enzymes regulated by negative feedback are robust to knockdown but susceptible to inhibition. Using the Raf–MEK–ERK kinase cascade as a model system, we find that ERK activation is resistant to genetic knockdown of MEK but susceptible to a comparable degree of chemical MEK inhibition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…4 and 6). The notion that DUSP5 (and likely other MKP/DUSPs) should mediate effects through 'feedback relief' is perhaps to be expected in light of the number of studies demonstrating that pharmacological inhibitors of the ERK pathway cause similar effects (25,30,36,37,45,46). Our results indicate that the nuclear sequestration of inactive ERK by DUSP5 evokes compensatory increases in upstream RAF and MEK activation through feedback relief ( Fig.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…4 and 6). The notion that DUSP5 (and likely other MKP/DUSPs) should mediate effects through 'feedback relief' is perhaps to be expected in light of the number of studies demonstrating that pharmacological inhibitors of the ERK pathway cause similar effects (25,30,36,37,45,46). Our results indicate that the nuclear sequestration of inactive ERK by DUSP5 evokes compensatory increases in upstream RAF and MEK activation through feedback relief ( Fig.…”
Section: Discussionmentioning
confidence: 57%
“…A major mechanism by which ERK self-limits its activity is through direct phosphorylation and inhibition of upstream components, such as RAS exchange factors (7), RTKs (8,9), and RAF kinases, which prevent RAS-mediated RAF dimerization and activation (4)(5)(6). This rapid, negative feedback confers homeostatic control, such that pharmacological inhibition or a reduction in total ERK concentration causes strong compensatory increases in upstream kinase activity, which acts to maintain near constant p-ERK output levels (30,36,37). We therefore hypothesized that the nuclear sequestration and inactivation of ERK by DUSP5 may cause similar compensatory increases in upstream kinase activity, and that this may explain why cytoplasmic p-ERK levels are maintained or even prolonged in the presence of DUSP5.…”
Section: Dusp5 Propagates Erk Signaling By Relieving Upstream Kinasementioning
confidence: 99%
See 2 more Smart Citations
“…This negative loop (i) speeds up the response time, (ii) converts intrinsic switch-like activation kinetics into graded linear responses, (iii) conveys robustness to changes in rates of reactions within the NFA module, (iv) stabilises outputs in response to drug-induced perturbations, and also has therapeutic implications ( Figure 4). It was shown that the ERK negative feedback diminishes the effectiveness of RAF and MEK inhibitors [107], but also that the drug-effect is quite different depending on the inhibitor's mechanism of action [108]. In negative feedback configurations, competitive inhibitors tend to be more effective compared to gene knockdowns [108].…”
Section: Negative Feedback Amplifiermentioning
confidence: 99%